Kontribusi Media Sosial sebagai Media Promosi dalam mengikuti Event Olahraga Online Permata Free Throw Basketball Virtual National Open Championship 2020 - Hidayah, Ayu Nur; Rumini, Rumini (Universitas Negeri Semarang, 2023)
The online sports event Permata Free Throw Basketball Virtual National Open Championship 2020 is an event held for basketball lovers who are unable to take part in offline events during the pandemic. This study uses descriptive research methods with data collection techniques using surveys. The subjects in this study were participants who were registered as participants of the Permata Free Throw Virtual National Basketball Championship. Collecting data using a questionnaire instrument, with a reliability coefficient of 0.886. The data analysis technique used multiple linear regression analysis. The result of this research is that the social media that is widely used is Instagram with a percentage of 29% and from 4 elements, namely communication between social media managers and social media users, communication between social media users, brand equity, and brand attitude is included in the high category. So it can be concluded that social media contributes as a promotional medium to take part in the Permata Free Throw Basketball Virtual National Open Championship 2020.